The Values of Social Education in Scouting Activities in Darussalam Gontor Islamic Boarding School for Campus 2 - Abdul Rochman (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2018)
Humans are social creature. They cannot live alone and always need help and support from others, as well as in community life. Civilizations won’t be formed without any action of supporting and helping each other. Moreover, humans contradict each other and disagree with one another. Because they have different opinions in their moral education, habits, and nature. According to Surah Yunus verse 19 that: “And mankind was not but one community [united in religion], but [then] they differed. And if not for a word that preceded from your Lord, it would have been judged between them [immediately] concerning that over which they differ”. Therefor, a human being should have good characters in associating with others, so he needs community education in order to be able to socialize well. One of the goals of education and teaching in Pondok Modern Darussalam Gontor is “community-relation”. Pondok Modern Darussalam Gontor gives special attention to public education in all matters, academic and non-academic activities. Thus, Pondok Modern Darussalam Gontor established many useful activities to build students’ character, such as scouting. It has many goals and aims, one of them is to help teenagers to improve themselves, body, spirit, sense, and soul abilities of community-relation.